Comparison of Malay reserve enactment between states / Nurulatikah Rosli - Rosli, Nurulatikah (2020)
Malay Reserve Land is interpreted as a unique category of land within the limits of each State. This land is restricted from sale, lease, transfer of title and mortgage to non - Malays. There are various sections in Enactment for Malay Reserve Land which has been enacted by British. The purpose of Malay Reserve Enactment was provided is to prevent State Land in Malay Reservation Area from being disposed by any means to the non-Malay. This study was conducted to compare the Malay Reserve Enactment between states in Malaysia. It will discuss the differences of enactment between state. The main objectives of this research are to study on the definition of Malay and its implementation in various state’s enactment and the Federal Constitution, to analyse the exchange condition of Malay Reservation land in land conversion, and to map the spatial changes of Malay Reservation area in Kedah. It hoped that, with the identification of the decrease and some of the proposed ways of protecting Malay Reserve Land in this study, it would help the authorities to maintain and enhance the value of Malay Land Rights in the future. The study areas are located at the Peninsular Malaysia excluding Melaka and Pulau Pinang. The total area of Malay Reserve Land is 197,927 square kilometres (km²). The data used include size and categories of Malay Reserve Land. This research will determine on law and regulations involving Malay Reserve Enactment in order to locate the differences in its implementation. The methodology of this research is analysing all the data collected and come out with the comparative study about the implementation of Act 89 of the Federal constitution, throughout the states. The data collection for this study based on National Land Code 1965, Federal Constitution, MRE Perlis 1935, MRE F.M.S Cap 142 1933, MRE Kedah 1931, MRE Kelantan 1930, MRE Terengganu 1941 and MRE Johor 1936.